Test-retest and between-device reliability of Vmaxpro IMU at hip and ankle for vertical jump measurement - Villalon-Gasch, L.; Jimenez-Olmedo, J. M.; Olaya-Cuartero, J.; Pueo, B. (Sensors, 2023)
The ability to generate force in the lower body can be considered a performance factor in sports. This study aims to analyze the test-retest and between-device reliability related to the location on the body of the inertial measurement unit Vmaxpro for the estimation of vertical jump. Eleven highly trained female athletes performed 220 countermovement jumps (CMJ). Data were simultaneously captured by two Vmaxpro units located between L4 and L5 vertebrae (hip method) and on top of the tibial malleolus (ankle method). Intrasession reliability was higher for ankle (ICC = 0.96; CCC = 0.93; SEM = 1.0 cm; CV = 4.64%) than hip (ICC = 0.91; CCC = 0.92; SEM = 3.4 cm; CV = 5.13%). In addition, sensitivity was higher for ankle (SWC = 0.28) than for the hip method (SWC = 0.40). The noise of the measurement (SEM) was higher than the worthwhile change (SWC), indicating lack of ability to detect meaningful changes. The agreement between methods was moderate (rs = 0.84; ICC = 0.77; CCC = 0.25; SEM = 1.47 cm). Significant differences were detected between methods (-8.5 cm, p < 0.05, ES = 2.2). In conclusion, the location of the device affects the measurement by underestimating CMJ on ankle. Despite the acceptable consistency of the instrument, the results of the reliability analysis reveal a significant magnitude of both random and systematic error. As such, the Vmaxpro should not be considered a reliable instrument for measuring CMJ.